Transcriptome reveals the immune and antioxidant effects of residual chlorine stress on Cyclina sinensis - Wang, Siting; Ren, Guoliang; Li, Desheng; Fan, Sishao; Yan, Susu; Shi, Junjie; Liu, Meimei; Dong, Zhiguo (Frontiers in Marine Science, 2023)
Residual chlorine is a common by-product of warm drainage in coastal nuclear power plants. when accumulating to some limit, it may threaten marine ecosystem especially for benthic clam. However, there are few studies on the molecular mechanisms related to immunity and antioxidant of residual chlorine stress on clams. In this study, the clam (Cyclina sinensis) was exposed for 96 h at different concentrations (0, 50, 100, 150, 200, 250, 300, 350, 400, 450 and 500 mg/L) of residual chlorine to observe its mortality, measure the activity of antioxidant and immune-related enzymes, and analyses the gene expression level in the hepatopancreas by using the transcriptome sequencing. The results showed that the mortality rate increased with the increase of stress time and concentration, and the mortality rate in the 400, 450 and 500 mg/L groups reached 100% at 96 h. The tolerance to residual chlorine of C. sinensis decreased with the increase of chlorine dioxide concentration, and the LC50 of 96 h was 217.6 mg/L by linear regression method. After residual chlorine stress, the activity of antioxidant-related enzymes (T-AOC and SOD) in the hepatopancreas showed a trend of first increase and then decrease with the extension of stress time. The immune-related enzyme activities of AKP and LZM showed a downward trend between 0 and 96 h, while the ACP enzyme activity showed a trend of first rising and then decreasing. Transcriptome analysis showed that residual chlorine stress significantly changed the expression levels of immune-related molecules associated with signal transduction, prophenoloxidase cascade, cell apoptosis and pattern recognition protein/receptor. Moreover, glutathione S-transferase (GST), heat shock protein (HSP) and other antioxidant-related genes were significantly affected under residual chlorine stress. This study provided valuable information for understanding the effects of residual chlorine stress on survival, physiological metabolism and molecular mechanisms of immune and antioxidant functions of C. sinensis.